Small Cetacean in a Human High-Use Area: Trends in Harbor Porpoise Abundance in the North Sea Over Two Decades - Nachtsheim, Dominik A.; Viquerat, Sacha; Ramírez-Martínez, Nadya C.; Unger, Bianca; Siebert, Ursula; Gilles, Anita (Frontiers in Marine Science, 2021)
The North Sea is one of the most heavily used shelf regions worldwide with a diversity of human impacts, including shipping, pollution, fisheries and offshore constructions. These stressors on the environment can have consequences for marine organisms, such as our study species, the harbour porpoise (Phocoena phocoena), which is regarded as a sentinel species and hence has a high conservation priority in the European Union (EU). As EU member states are obliged to monitor the population status, the present study aims to estimate trends in absolute harbour porpoise abundance in the German North Sea based on almost two decades of aerial surveys (2002-2019) using line-transect methodology. Furthermore, we were interested in trends in three Natura2000 Special Areas of Conservation (SACs), which include the harbour porpoise as designated feature. Trends were estimated for each SAC and two seasons (spring and summer) as well as the complete area of the German North Sea. For the trend analysis we applied a Bayesian framework to a series of replicated visual surveys, allowing to propagate the error structure of the original abundance estimates to the final trend estimate and designed to deal with spatio-temporal heterogeneity and other sources of uncertainty. In general, harbour porpoise abundance decreased in northern areas and increased in the south, such as in the SAC Borkum Reef Ground. A particularly strong decline with a high probability (94.9%) was detected in the core area and main reproduction site in summer, the SAC Sylt Outer Reef (-3.79% per year). The overall trend for the German North Sea revealed a decrease in harbour porpoise abundance over the whole study period (-1.79% per year) with high probability (95.1%). The assessment of these trends in abundance based on systematic monitoring should now form the basis for adaptive management, especially in the SAC Sylt Outer Reef, where the underlying causes and drivers for the large decline remain unknown and deserve further investigation, also in a regional North Sea wide context.